2011
DOI: 10.1016/j.ijheatmasstransfer.2011.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative heat and mass transfer from the free surface of a liquid wicked into a bed of spheres

Abstract: Evaporation of ethanol from square packed arrays of 3.95 mm diameter copper spheres in a transparent, enclosed chamber is investigated. The enclosure ensures that relatively saturated vapor conditions exist near the free surface. The desired heat flux is imposed on the copper substrate upon which the copper spheres are mounted, and the liquid level in the bed is maintained by wicking from a continuous supply of liquid provided by a syringe pump.Transparent windows in the enclosure allow for visualization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Iverson et al [30] experimentally quantified evaporation rates from sintered wick samples under conditions simulating heat pipe operation. Furthermore, Davis and Garimella [31] measured evaporative thermal resistance of wicks of different porosities under saturated vapor conditions, while Migliaccio and Garimella [32] mapped out the evaporative performance of an organized bed of copper spheres. Hanlon and Ma [33] performed experiments and developed a simple numerical model to delineate the role of thin-film evaporation in sintered media.…”
Section: Capillary Pressure and Evaporative Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Iverson et al [30] experimentally quantified evaporation rates from sintered wick samples under conditions simulating heat pipe operation. Furthermore, Davis and Garimella [31] measured evaporative thermal resistance of wicks of different porosities under saturated vapor conditions, while Migliaccio and Garimella [32] mapped out the evaporative performance of an organized bed of copper spheres. Hanlon and Ma [33] performed experiments and developed a simple numerical model to delineate the role of thin-film evaporation in sintered media.…”
Section: Capillary Pressure and Evaporative Heat Transfermentioning
confidence: 99%
“…Evaporation from the thin-film region of a liquid meniscus has been shown in a number of prior studies (e.g., Refs. [32,56,57]) to be the dominant mode of phase-change heat transfer from thin wick layers. Ranjan et al [55] observed that an approximately 20% area of the meniscus near the triple line contributes to more than 80% of the overall evaporative heat transfer from the entire meniscus.…”
Section: Wicking and Evaporation Characteristicsmentioning
confidence: 99%